UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL UMBI BAWANG DAYAK (Eleutherine palmifolia) TERHADAP MENCIT YANG DIINDUKSI KARAGENIN - Milasari, Novi; Adhila, Ghina; Syamsul, Eka Siswanto (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Inflammation is a normal response to protect tissue injury from toxic chemicals, physical trauma, or microbial agents. Treatment of inflammation generally uses synthetic drugs, but the use of these drugs in addition to eliminating inflammation also has many side effects and is relatively expensive. Therefore, anti-inflammatory drugs derived from plants are used. One of the natural medicines used is Dayak onion (Eleutherine palmifolia) because empirically it is widely used by the Dayak and Kutai communities, which has the potential as a medicinal plant with various enormous properties. This study aimed to determine the anti-inflammatory activity of an ethanol extract of Dayak onion bulbs (Eleutherine palmifolia) in carrageenin-induced mice. The test of anti-inflammatory activity was carried out by forming artificial inflammation on the soles of the feet of white mice. The study was conducted on 15 mice, which were divided into 5 groups. The first group as a negative control was given a 0.5% CMC solution. The second group as a positive control was given diclofenac sodium at a dose of 27 mg/ 20 g BW. The third, fourth, and fifth groups were given a dayak onion bulb extract dose of 100 mg /kgBB, 200 mg /kgBB, and 400 mg /kgBB. Based on the measurement of the percent inhibition of inflammation from the 30th minute to the 300th minute, it was found that the average dose of Dayak onion extract 1 (100 mg/KgBB) had the lowest percent inhibition of inflammation, which was 23.064±1.286%, dose 2 was 37.701±2.354%, and dose 3 was 52.324±4.751% and positive control of 76.348±8.702% which has the highest percent of inflammation inhibition. Based on the study, it can be concluded that the ethanol extract of dayak onion bulbs has the best anti-inflammatory activity at dose 3 of 52.324±4.751% in mice induced by carrageenin.